Research on Data Fusion Algorithm of Intelligent Building Based on Internet of Things Technology - Zhuang, Jianyou (International Journal of Informatics and Information Systems, 2023)
In an era of sustained economic growth and rising living standards, the demand for housing continues to increase significantly, driving the development of the construction industry and the inevitable transformation of architectural digitization as a prevailing trend. This circumstance has generated limitless economic opportunities across various construction-related sectors, including building materials, technology, and related services. Simultaneously, the evolving Internet of Things (IoT) technology has paved the way for the digitization of buildings, revolutionizing the entire process of architectural design, construction, and management. Architectural digitization enables real-time monitoring, in-depth data analysis, and the optimization of building efficiencies, encompassing energy management, temperature control, and lighting systems. In the current landscape, architectural digitization has given rise to smart buildings that can effectively control nearly all aspects, from temperature and lighting to security systems and comfort. Furthermore, IoT technology has facilitated addressing sustainability challenges by enabling more efficient and sustainable energy management—an essential aspect of the journey toward environmentally friendly buildings. Nevertheless, on the path to fully interconnected digital buildings, there are challenges that must be addressed, such as data security and user privacy, both of which require special attention. Looking forward, research directions include the development of more sophisticated digital integration algorithms, enhanced data security, and the integration of artificial intelligence into building management. The future of architectural digitization holds great promise, with the potential to create more efficient, secure, and environmentally friendly buildings. To achieve these goals, it is essential to strengthen cross-sector collaboration, receive government support, and emphasize research and innovation in the field of architectural digitization.